Improved immunocompatibility of active targeting liposomes by attenuating nucleophilic attack of cyclic RGD peptides on complement 3 - Meng, Nana; Lu, Jiasheng; Zhou, Jianfen; Yang, Shengmin; Zhang, Chen; Jia, Ruiyi; Ding, Yuan; Bao, Yanning; Wang, Jun; Ma, Xiaopei; Chen, Ruohan; Jiang, Zhixuan; et al. (Biomaterials, 2025)
One of the challenges for the clinical translation of active targeting nanomedicines is the adverse interactions between targeting ligands and blood components. Herein, a novel regularity, which reveals the interactions between cyclic RGD (Arg-Gly-Asp) peptide-modified liposomes and complement components in blood, is reported. As the nucleophilicity of arginine guanidine group within the cyclic RGD-like peptide increases, targeting liposomes potentiate complement cascade via the amplification loop of complement 3 (C3), ultimately leading to accelerated blood clearance, increased deposition in the reticuloendothelial system (RES) organs, enhanced immune responses, and potential side effects. By appropriately reducing the nucleophilicity of guanidine group, cyclic R2 peptide is designed for modification of liposomes to target integrin αvβ3. Compared to the widely used targeting molecule c(RGDyK), R2 eliminates the negative effects of C3 opsonization and specific antibody production, significantly improves the in vivo immunocompatibility of targeting liposomes, and demonstrates superior anti-tumor efficacy in mouse models of orthotopic breast cancer and glioma. Thus, the proposed regularity of interactions between guanidine nucleophilicity and C3, along with the successful application of the low complement activation capacity targeting ligand R2, provides new insights for addressing challenges related to complement activation in the clinical translation of active targeting nanomedicines. [Display omitted]